Development of an E-Module Based on a Realistic Mathematics Education Approach to Improve the Literacy Skills of Junior High School Students - Mahardika, Putri; Fauzi, Kms Muhammad Amin (Journal of Education Technology Information Social Sciences and Health, 2024)
This study aims to determine the validity, practicality, and effectiveness of e-modules based on the Realistic Mathematics Education approach so that it can improve the statistical literacy skills of junior high school students. The research instruments used were media validation sheets, material validation sheets, statistical literacy test instrument validation sheets, and questionnaires on teacher and student responses to the developed media. The research design used is Research and Development with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The subject of the study is 18 students in grades VIII-2 of SMP Prayatna Medan in the even semester of the 2023/2024 school year. The results of the research conducted showed that the e-module based on the Realistic Mathematics Education approach developed met the validity criteria based on the percentage of validity assessment of media experts of 92.08% and material experts of 86.66% with a very valid category. Met the practicality criteria based on the assessment of teacher response of 90% and student response of 90.34% with the category of very practical and met the effectiveness criteria based on the achievement of student learning completeness classically reaching an average percentage of 89%, achievement of learning indicators or objectives of 84.37%, teacher's ability to manage learning by 90.15%, and positive student response to e-module by 95%. The improvement of students' statistical literacy skills provided through e-modules based on the Realistic Mathematics Education Approach obtained an average increase of 34.37 from the initial ability test (Pretest) with an average score of 43.75 increased to 78.15 in the final ability test (Posttest). From all statistical literacy indicators, an average N-Gain of 0.798 was obtained in the high category.